2000
DOI: 10.1063/1.1311600
|View full text |Cite
|
Sign up to set email alerts
|

Two-step growth of high-quality GaN by hydride vapor-phase epitaxy

Abstract: The use of a low-temperature layer of GaN formed by hydride vapor-phase epitaxy (HVPE) as a template to grow high-quality HVPE films is demonstrated. Using layers formed by reacting GaCl and NH3 at 550 °C and annealed at a growth temperature of 1050 °C, thick films of GaN can be grown by HVPE with fewer than 108 dislocations per cm2. Dislocation densities measured by high-resolution x-ray diffraction, atomic-force microscopy step termination density and plan-view transmission electron miscroscopy reveal that ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…FWHM values of w-rocking curves of 266 00 and of w/2q scans of 192 00 have been achieved. These values indicate the high crystalline quality achieved and compare well with results reported from GaN layers grown by HVPE [6] and MOVPE [3].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…FWHM values of w-rocking curves of 266 00 and of w/2q scans of 192 00 have been achieved. These values indicate the high crystalline quality achieved and compare well with results reported from GaN layers grown by HVPE [6] and MOVPE [3].…”
Section: Resultssupporting
confidence: 77%
“…Thus, in this first step a crystalline layer which supplies high-density GaN seeds having the same orientation as the substrate is obtained. It has been reported in [6] that the heat-up process was found to be particulary critical for the buffer layer formation. SEM observation from interrupted heat-up processes have shown no remarkable change of the surface during the heat-up in our case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a GaCl-pretreatment or a ZnO layer [1] were used to aid nucleation. Later low-temperature nucleation processes were established for direct growth on sapphire in HVPE [2]. However, lattice mismatch and thermal expansion differences result usually in cracks and wafer bending in thick GaN layers.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative method, which does not require photolithography, is the two step deposition process involving growth of a low temperature (LT) GaN buffer layer. This technique has been used in both metal organic chemical vapor deposition (MOCVD) [15,16] and HVPE [17]. Using this technique, it has been shown that for thicker GaN layers (> 600 µm) the bulk GaN layer is spontaneously separated from the substrate which means that many time-consuming or complicated process steps such as mechanical lapping of sapphire [18], chemical etching [19], laser lift-off [20], ELOG [21,22] and void assisted separation [23] can be avoided.…”
Section: Introductionmentioning
confidence: 99%